2019
DOI: 10.1038/s41598-019-44127-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity in Stomatal Density among Soybeans Elucidated Using High-throughput Technique Based on an Algorithm for Object Detection

Abstract: The stomatal density (SD) can be a promising target to improve the leaf photosynthesis in soybeans ( Glycine max (L.) Merr). In a conventional SD evaluation, the counting process of the stomata during a manual operation can be time-consuming. We aimed to develop a high-throughput technique for evaluating the SD and elucidating the variation in the SD among various soybean accessions. The central leaflet of the first trifoliolate was sampled, and microscopic images of the leaflet replica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 24 publications
0
39
0
Order By: Relevance
“…Meanwhile, Fetter et al (2019) have utilized a convolutional neural network (CNN), a deep learning architecture, to identify stomata from a variety of microscopic images taken from various plant species. Other deep learning models, e.g., YOLO, SSD, and Mask R-CNN, have been proposed as useful adjuncts in stomata detection and trait measurement ( Sakoda et al, 2019 ; Casado-García et al, 2020 ; Jayakody et al, 2021 ). As exemplified by those studies, deep learning has been demonstrated to be efficacious in the quantification of stomatal traits.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Fetter et al (2019) have utilized a convolutional neural network (CNN), a deep learning architecture, to identify stomata from a variety of microscopic images taken from various plant species. Other deep learning models, e.g., YOLO, SSD, and Mask R-CNN, have been proposed as useful adjuncts in stomata detection and trait measurement ( Sakoda et al, 2019 ; Casado-García et al, 2020 ; Jayakody et al, 2021 ). As exemplified by those studies, deep learning has been demonstrated to be efficacious in the quantification of stomatal traits.…”
Section: Introductionmentioning
confidence: 99%
“…Stomatal pore area measurements require the identification of stomata in a microscope image ( Dow et al, 2014 ); with a small number of stomata, this can be achieved using manual image analysis tools. More recently, higher order image processing and machine learning has been used to automate this process ( Laga et al, 2014 ; Liu et al, 2016 ; Jayakody et al, 2017 ; Toda et al, 2018 ; Fetter et al, 2019 ; Sakoda et al, 2019 ). In this work, a CNN ( Lecun et al, 1998 ) based on the MATLAB® implementation of the AlexNet ( Krizhevsky et al, 2012 ) network was used to identify stomata ( MathWorks, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Whether it be through detecting the unique fluorescence emission of stomatal guard cells under UV excitation ( Karabourniotis et al, 2001 ), through rhodamine 6G staining ( Eisele et al, 2016 ), or through template matching ( Laga et al, 2014 ), it has ultimately been the automatic measurement, not detection, of stomatal pores in large samples that has proven most difficult. More recent research ( Jayakody et al, 2017 ; Toda et al, 2018 ; Fetter et al, 2019 ; Sakoda et al, 2019 ) utilizes machine learning and image processing to detect stomata (and sometimes classify the state of the stomata) in microscope images. The accuracy levels achieved in these studies shows promise and enables plant scientists to conduct high-throughput analysis for stomata detection.…”
Section: Introductionmentioning
confidence: 99%
“…A crystal-clear tape was used as the desired area of the leaf surface and drawn off carefully. A 1 mm 2 grid was superimposed on the images for the calculation of stomata density [31]. Some example of captured imprint is shown in Figure 1.…”
Section: Datasetmentioning
confidence: 99%